2021
DOI: 10.3390/w13162263
|View full text |Cite
|
Sign up to set email alerts
|

A Spatial Integrated SLR Adaptive Management Plan Framework (SISAMP) toward Sustainable Coasts

Abstract: Sea-level rise (SLR) is known as a central part of the Earth’s response to human-induced global warming and is projected to continue to rise over the twenty-first century and beyond. The importance of coastal areas for both human and natural systems has led researchers to conduct extensive studies on coastal vulnerability to SLR impacts and develop adaptation options to cope with rising sea level. Investigations to date have focused mostly on developed and highly populated coasts, as well as diverse ecosystems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
(94 reference statements)
0
0
0
Order By: Relevance
“…Yet, avoidance is a proactive approach that may prevent development or rebuilding in hazard zones, such as flood plains or areas that would be inundated by SLR. Davar et al [21] presented a case study in Southern Iran, along the Gulf of Oman, which is a coastal area with a low level of development. The study uses types of lands exposed to the high-end estimates of SLR by 2100 as the primary criteria for determining adaptation approaches and ways to develop the coast in the future, identifying areas that could be developed but would be threatened by SLR, and including principles of spatial land management such as land evaluation, suitability, and planned use.…”
Section: Exposure To Coastal Hazardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, avoidance is a proactive approach that may prevent development or rebuilding in hazard zones, such as flood plains or areas that would be inundated by SLR. Davar et al [21] presented a case study in Southern Iran, along the Gulf of Oman, which is a coastal area with a low level of development. The study uses types of lands exposed to the high-end estimates of SLR by 2100 as the primary criteria for determining adaptation approaches and ways to develop the coast in the future, identifying areas that could be developed but would be threatened by SLR, and including principles of spatial land management such as land evaluation, suitability, and planned use.…”
Section: Exposure To Coastal Hazardsmentioning
confidence: 99%
“…These articles demonstrate that, without proper understanding of data and limitations, project developers and decision makers may overvalue investments in adaptation and, as result, science may not necessarily translate into effective adaptation implementation. Acosta et al demonstrated that precise digital elevation mapping (DEM) data are needed for targeted local-level decisions, but cost-effective, national data can be used by planners in the absence of high-resolution data to support adaptation action planning (e.g., as in [21]), possibly saving critical funding for project implementation.…”
Section: Exposure To Coastal Hazardsmentioning
confidence: 99%